2014
DOI: 10.3109/14017431.2013.871058
|View full text |Cite
|
Sign up to set email alerts
|

Interval training does not modulate diastolic function in heart transplant recipients

Abstract: The study does not support a role of diastolic dysfunction in the limited exercise capacity of HTx recipients and suggests that in these patients peripheral factors are of greater importance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 26 publications
1
16
0
Order By: Relevance
“…This was also the conclusion in a recent study of predictors of VO 2peak in HTx recipients . Further, we have recently shown that echocardiographic parameters during rest or during exercise are not affected by exercise training, despite considerable effect on VO 2peak , confirming that the effects of exercise are primarily peripheral and not through cardiac remodeling.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…This was also the conclusion in a recent study of predictors of VO 2peak in HTx recipients . Further, we have recently shown that echocardiographic parameters during rest or during exercise are not affected by exercise training, despite considerable effect on VO 2peak , confirming that the effects of exercise are primarily peripheral and not through cardiac remodeling.…”
Section: Discussionsupporting
confidence: 87%
“…Studies on HTx recipients participating in exercise rehabilitation suggest both central and peripheral adaptations to explain the improved exercise capacity . Currently, the physiological mechanisms are not fully understood.…”
Section: Discussionmentioning
confidence: 99%
“…Among the 13 included trials, 6 had an unclear risk of selection bias, [15][16][17][18][19][20] 1 had a high risk of selection bias, 21 and 7 failed to describe concealed random allocation. 17,[19][20][21][22][23][24] In addition, 1 trial had an unclear risk of attrition bias, 19 and 1 trial had a high risk of reporting bias.…”
Section: Methodological Qualitymentioning
confidence: 99%
“…Exercise capacity is generally limited to approximately 50-70% of the age-predicted value in HTX patients despite normal LV ejection fraction (LVEF) and independent of the presence of cardiac allograft vasculopathy (CAV) [10][11][12][13][14][15]. It has been speculated that the reduction in exercise capacity observed in HTX patients may be caused by elevated LV-FP [7,16,17].…”
Section: Introductionmentioning
confidence: 99%